Field investigation to determine the environmental source of PCBs in a pig farm. (15th April 2018) - Vaccher, Vincent; Marchand, Philippe; Picherot, Mélanie; Dervilly-Pinel, Gaud; Lesquin, Elodie; Brosseaud, Aline; Venisseau, Anaïs; Le Bizec, Bruno
Graphical abstract: Highlights: Non-compliant pig fat for the sum PCDD/F and DL-PCB resulted in farm investigations. A range of possible sources was characterized by GC-HRMS for PCB levels. Peeling feed storage tank paints were discovered to be the PCB source. Abstract: During a national monitoring plan, a pork fat sample was declared non-compliant for the sum of dioxins and PCB-DL (EU regulation). The National Reference Laboratory together with competent authorities conducted extended investigations to determine rapidly the contamination source at the farm level. A range of samples ( n = 129), representative of potential contamination sources, was selected for further characterization (fat, feed, materials, dust, soil) and was analyzed for PCDD/Fs and DL-PCBs by GC-HRMS. A hot spot was localized in the farm, which corresponded to a pre-feed storage tank, the paints of which presented huge DL-PCB concentrations (>1 × 10 6 pg g −1 ), responsible for the contamination. The present case report describes a new source of PCB contamination, previously undescribed.